Biventricular circulatory support using single-device and dual-device configurations: Initial pump characterization in simulated heart failure model - Karimov, Jamshid H.; Miyagi, Chihiro; Flick, Christine R.; Polakowski, Anthony R.; Kuban, Barry D.; Kuroda, Taiyo; Horvath, Dennis W.; Fukamachi, Kiyotaka; Starling, Randall C. (Frontiers in Cardiovascular Medicine, 2023)
Objective: The biventricular assist device (BVAD) is a treatment option for severe biventricular heart failure (BHF). We are developing a universal ventricular assist device (UVAD)--intended for left and/or right ventricular assistance--and a continuous-flow total artificial heart (CFTAH) for total cardiac replacement. Herein, we compare the in vitro hemodynamic performance of two UVADs and a CFTAH, used as a BVAD. Methods: The biventricular mock circulatory loop used for this study uses two pneumatic pumps (Abiomed AB5000™, Danvers, MA, USA) driven by a dual-output driver (Thoratec Model 2600, Pleasanton, CA, USA) to simulate the heart failure (left – LHF; right – RHF) conditions. Four different systolic BHF conditions were simulated. For each condition, CFTAH and UVAD configurations were tested at two different speeds, and both ventricular and atrial cannulations were tested. Results: Hemodynamic requirements were met with both CFTAH and UVAD configurations. The left and right UVAD configuration provided better atrial balance in LHF and RHF. In moderate and severe BHF conditions, both the CFTAH and dual UVADs provided optimal atrial pressure balance. However, the CFTAH did not achieve an appropriate atrial pressure balance when cannulated in the atrial position in LHF and RHF. Conclusions: This extensive in vitro testing of the two BVAD systems demonstrated optimal device performance and self-regulation for both single and dual-device support configurations in BHF. For moderate and severe BHF, both devices performed well with regard to output and atrial pressure regulation. However, the dual-device configuration provided better atrial pressure balance under all tested BHF conditions.